RETRACTED: Empirical analysis of the impact of China–Japan–South Korea transportation infrastructure investment on environmental degradation and the validity of the environmental Kuznets curve hypothesis - Lu, Hongbo; Liu, Yuanhao; Ali, Arshad; Tian, Rongzhi; Chen, Yuanchun; Luo, Yuanwei (Frontiers in Psychology, 2022)
Building sustainable and affordable transport systems is a key issue for social development and sustainable urban expansion. The study used Dynamic Ordinary Least Squares (DOLS) and Fully Modified Ordinary Least Squares (FMOLS) to examine the impact of transport infrastructure investment on environmental degradation in China, Japan, and South Korea over the period 1995-2020 and the validity of the EKC hypothesis. The results show that GDP has a significant positive effect, and GDP2 and GDP3 have significant adverse effects on environmental degradation, respectively. These results confirm the validity of the inverted U shaped EKC hypothesis in selected Asian countries. Road infrastructure investment has a significant positive effect, while railway infrastructure investment has a significant adverse effect on environmental degradation. Air infrastructure investment and trade opening have a progressive and statistically significant impact on environmental pollution. Modern rail systems that run on electricity are considered less polluting, so the share of rail infrastructure investment in the transport mix can help build sustainable and safe transport systems at the city Centre and intercity levels and reduce emissions in Asian countries. Moreover, strict enforcement of the prevailing environmental conditions of trade agreements should be encouraged to reduce the increasing impact of free trade on environmental pollution.